1996
DOI: 10.1177/0148558x9601100205
|View full text |Cite
|
Sign up to set email alerts
|

The 1990 Pennsylvania Antitakeover Law: Should Firms Opt Out of Antitakeover Legislation?

Abstract: This paper examines the firm's opting out decision and the impact of the 1990 Pennsylvania Antitakeover Law on the stock prices of 123 firms. The results indicate that on average Pennsylvania stock returns decreased by 9 percent from introduction to passage. A comparison indicates that firms that opted out had CARs 18 percentage points higher than firms that chose not to opt out. The event study methodology may not be appropriate because investors may anticipate the passage of legislation and because there may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Staggered boards are shown to increase substantially the likelihood that a target receiving a hostile bid would remain independent. 23 Szewczyk and Tsetsekos (1992), Karpoff and Malatesta (1990), and Swartz (1996) all found that passage of the Pennsylvania statute was accompanied by a substantial reduction in the value of Pennsylvania firms. Ryngaert and Netter (1990) reached a similar conclusion with respect to the passage of the Ohio legislation.…”
Section: Extreme Statutesmentioning
confidence: 99%
“…Staggered boards are shown to increase substantially the likelihood that a target receiving a hostile bid would remain independent. 23 Szewczyk and Tsetsekos (1992), Karpoff and Malatesta (1990), and Swartz (1996) all found that passage of the Pennsylvania statute was accompanied by a substantial reduction in the value of Pennsylvania firms. Ryngaert and Netter (1990) reached a similar conclusion with respect to the passage of the Ohio legislation.…”
Section: Extreme Statutesmentioning
confidence: 99%
“…Other estimates of the advantage to opting out are higher. For example, Swartz (1996) finds that firms that opted out had 18 percent higher stock returns than firms that did not opt out over a 190‐day event window containing passage of the Act.…”
mentioning
confidence: 99%
“…Yet, most studies find that bidder gains are either insignificant or slightly negative when the target is publicly listed. The potential reasons for this perplexing outcome include takeover regulation (Jarrell and Bradley, 1980;Swartz, 1996;Humphery-Jenner, 2012), anticipation of the transaction (Cai et al, 2011), negative signal about the acquirer's share price (Asquith et al, 1983;Myers and Majluf, 1984;Travlos, 1987;Shleifer and Vishny, 2003;Jensen, 2005), negative signal about the acquirer's internal growth prospects (McCardle and Viswanathan, 1994;Jovanovic and Braguinsky, 2002), competition among bidders (Bradley et al, 1988;Jarrell and Poulsen, 1989), price pressure from merger arbitrage (Mitchell et al, 2004), managerial optimism (Heaton, 2002), managerial mistake (Weston et al, 2004), hubris and overconfidence (Roll, 1986;Malmendier and Tate, 2008) and agency problems (Jensen, 1986;Morck et al, 1990;Jensen, 2005;Masulis et al, 2007;Baker et al, 2012;Harford et al, 2012;Phalippou et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%